The Activist Polis: Topologies of Conflict in Indigenous Solidarity Activism. Issue 1 (15th June 2015) - Mott, Carrie
Abstract: Interpersonal conflict poses a serious threat to social justice activism. In the context of indigenous solidarity activism in southern Arizona, conflicts are often born of the challenges accompanying differentials in social privilege due to differences in race and ethnicity relative to white supremacist settler colonialism. This paper examines activist collaboration between Tohono O'odham and non‐Native anarchist activists in southern Arizona, arguing that a topological activist polis is a useful lens through which we can better understand the roots of conflict in social justice activism. Non‐Native activists are often aware of the ways white supremacist settler colonial society privileges particular identities while marginalizing others. Nonetheless, settler and white privilege give rise to tensions which can be seen topologically through the very different relationships non‐Native and indigenous activists have to ongoing processes of white supremacy and to histories of the genocide of indigenous peoples.